The structure of ecnomics : a mathematical analysis - Silberberg, Eugene; Suen,Wing. (NewDelhi : Mcgraw hill education (india) pvt ltd, 2014)
This text combines mathematical economics with microeconomic theory and can be required or recommended as part of a course in graduate microeconomic theory, advanced undergraduate or graduate-level mathematical economics, or any advanced topics course. It also has reference value for international, library, professional and reference markets. This revision addresses significant new topics--the theory of contracts and markets with imperfect information--that have recently become prominent in the microeconomics literature.
Includes index.
Keywords: Economics